Afribank Point of Sale support system - Chikwana, Keith P (Midlands State University, 2020)
Agribank POS Support system is a system that is used to manage and support the use of all Agribank POS machines that is from when the branch requests POS machines for their clients to the issuance of the POS machines. This system targeted the various departments in the bank (Branch, E-banking, E-channels and Audit) and production of reports for all the levels of management. The purpose of this project was to come up with an efficient and effective Agribank POS system that would meet the user’s needs timelessly. This project was done in five main phases, which are Introduction, Planning, Analysis, Design and Implementation Phases. The introduction phase is an introduction of the research study and a historical background of the organization. The planning phase details the scheduling of the study and a feasibility study which was conducted to evaluate viability of the system. From the feasibility study, the project proved to be feasible. During the analysis phase, the researcher analyzed the weaknesses and strengths of the current or existing system and evaluated whether to develop, improve or outsource the software. User requirements were gathered using questionnaires, interviews and observations. After analysis phase, the design phase followed. A database was designed using MSSQL Database management system, input forms, menus and output forms using diagrams to illustrate the major functionalities of the Agribank POS system. The last phase was implementation, where the implementation of the proposed system, testing and maintenance were carried out continuously identifying and rectifying any errors. Parallel conversion was recommended when the project was implemented.